Zirconia-Reinforced Lithium Silicate Ceramic - A 2-Year Follow-up of a Clinical Experience with Anterior Crowns - Saavedra, Guilherme de Siqueira Ferreira Anzaloni; Rodrigues, Flávia Pires; Bottino, Marco Antonio (My University, 2017)
The aim of this manuscript is to describe 2-year follow-up of a clinical experience with a zirconia-reinforced lithium silicate ceramic for an anterior rehabilitation with single metal-free crowns. The maxillary-central incisor teeth crowns were made by zirconium-reinforced lithium silicate and covered with porcelain were obtained with a digital impression with the intra-oral scanner of the CEREC system as a basis for virtual design, as well as a laminate for the left lateral maxillary incisor, based on a double scanning technique. Lithium silicate material seems to be a safe and satisfactory alternative for anterior crowns' rehabilitation.
Keywords: Aesthetic Dentistry; Anterior Crowns; Dental Ceramics; Rehabilitation; Zirconia